3D printed bioceramics fabricated using negative thermoresponsive hydrogels and silicone oil sealing to promote bone formation in calvarial defects. Issue 4 (15th February 2021) - Lin, Che-Wei; Su, Yu-Feng; Lee, Chih-Yun; Kang, Lin; Wang, Yan-Hsiung; Lin, Sung-Yen; Wang, Chih-Kuang
Abstract: The purpose of the present work was to investigate the potential for application and the effectiveness of osteoconductive scaffolds with bicontinuous phases of 3D printed bioceramics (3DP-BCs) based on reverse negative thermoresponsive hydrogels (poly[( N -isopropylacrylamide)- co-( methacrylic acid)]; p(NiPAAm-MAA)). 3DP-BCs have bioceramic objects and microchannel pores when created using robotic deposition additive manufacturing. We evaluated the benefits of silicone oil sealing on the 3DP-BC green body during the sintering process in terms of densification and structural stability. The shrinkage, density, porosity, element composition, phase structure and microstructural analyses and compression strength measurements of sintered 3DP-BC objects are presented and discussed in this study. In addition, the results of cell viability assays and bone healing analyses of the calvarial bone defects in a rabbit model were used to evaluate 3DP-BC performance. The main results indicated that these 3DP-BC scaffolds have optimal continuous pores and adequate compressive strength, which can enable the protection of calvarial defects and provide an environment for cell growth. Therefore, 3DP-BC scaffolds have better new bone regeneration efficiency in rabbit calvarial bone defect models than empty scaffolds and mold-forming bioceramic scaffolds (MF-BCs).